Influence of Risk Management on Project Implementation, a Case Study of Indoor Residual Spraying Project in Rwanda (International Journal of Scientific Research and Management (IJSRM), 2022)
The study entitled “Influence of Risk Management on Project Implementation, a case of Indoor Residual Spraying (IRS) Project in Rwanda”. The purpose of the study was to investigate the influence of project risk management on project implementation in Rwanda with reference to Indoor Residual Spraying (IRS) Project. The study was guided by four specific objectives: to examine the influence of project risk identification on implementation of Indoor Residual Spraying (IRS) Project, to assess the influence of Project Risk Analysis on the implementation of Indoor Residual Spraying (IRS) Project, to find out the influence of project risk response planning on the implementation of Indoor Residual Spraying (IRS) Project and to ascertain the influence of Project risk monitoring and control on the implementation of Indoor Residual Spraying (IRS) Project. The research designs that were used in this study are descriptive research design and analytical research design. The study used 83 employees of Indoor Residual Spraying (IRS) Project as sample size. The study used stratified sampling techniques to select whole population to participate in this study. The study used questionnaires, interview guide and documentary review as method of data collection and finally the study used descriptive statistics and inferential statistics such as correlation analysis and multiple linear regression analysis as method of data analysis. For the first objective, the findings revealed that there existed a significant moderate positive correlation (R = 0.552**, p-value=0.002<0.01) between project risk identification and implementation of (IRS) Project and also results revealed that project risk identification have significance positive effect on implementation of (IRS) Project as indicated by β1= 0.199, p=0.000<0.05, t= 3.257. The implication is that an increase of one unit in project risk identification would lead to an increase in implementation of (IRS) Project by 0.199 units. For the second objective, the findings revealed that there existed a significant weak positive correlation (R = 0.375**,p-value=0.000<0.01) between project risk analysis and implementation of (IRS) Project and also the results revealed that project risk analysis have significance positive effect on implementation of (IRS) Project as indicated by β2=1.226, p=0.000<0.05, t=8.797. For the third objective, the findings revealed that there existed significant high positive correlation (R = 0. 797**,p-value=0.003<0.01) between project risk response and implementation of (IRS) Project and also the results revealed that project risk response planning have significance positive effect on implementation of (IRS) Project as indicated by β3= 0.396, p=0.000<0.05, t= 3.781. For the fourth objective, the findings revealed that the study established the existed of a strong positive correlation (R = 0.681**,p-value=0.001<0.01) between project risk monitoring & control and implementation of (IRS) Project and also the regression results revealed that project risk monitoring and control have significance positive effect on implementation of (IRS) Project as indicated by β4= 0.341, p=0.040<0.05, t= 2.085. As such, the project management team should explore ways for enhancing the effectiveness of the tools in risk analysis by providing more orientation of stakeholders on this.